Cardiac and Systemic Thrombus Caused by Drug Abuse - John Eliveha; Shravani Vindhyal; Mohinder Vindhyal (Case Reports in Cardiology)
Drug abuse is an increasing concern all over the world especially in the United States. Methamphetamine have been well established to cause elevated body temperature, irregular heartbeat, seizures, and heart disease. We present a case of ventricular thrombus with systemic emboli in a patient with dilated cardiomyopathy after methamphetamine use.